Koperasi Simpan Pinjam Bali Artha Guna dalam Bingkai Budaya Masyarakat Modern di Bali - Sunaryo, Fransiska Dewi Setiowati; Rai Wahyuni, Anak Agung Ayu (Humanis, 2021)
The purpose of this study is to reveal several problems related to the application of modern management in the management of Savings and Loans Cooperatives (KSP), especially in the KSP Puskopdit Bali Artha Guna (BAG). Puskopdit Bali Artha Guna is a secondary KSP which until the end of 2018 has 20 primary cooperative members with 58,520 individual members spread across Bali. Cooperatives as a form of business entity engaged in the economy have a management structure that is somewhat different from other business entities. To achieve the goals of cooperatives, it is necessary to apply a good management system, namely implementing management functions. Some of the problems described in the discussion include 1) in what ways the development of modern management has been carried out at KSP Puskopdit Bali Artha Guna; 2) how is the implementation of modern management practices in cooperatives in facing today's business competition; 3) what benefits can be generated for the community, especially cooperative members in Bali. The method used in this research is descriptive qualitative with the method of collecting data through literature studies and in-depth interviews. In general, members of the Puskopdit Bali Artha Guna cooperative have digitized and implemented modern management in their operational systems to remain competitive in the millennial era who are familiar with technology, so that they are able to compete with other financial institutions.